Adopsi Petani dalam Penggunaan Varietas Unggul Ubi Kayu Malaysia (Manihot Esculenta Crantz) di Kecamatan Sei Rampah, Kabupaten Serdang Bedagai, Provinsi Sumatera Utara - Mukhlis Yahya; Ameilia Zuliyanti Siregar; Darman Beriman Zega (AGRITEXTS: Journal of Agricultural Extension, 2021)
This study aims to determine the adoption of farmers and the factors that influence the adoption of farmers in the use of superior varieties of Malaysian cassava. This study was conducted in Sei Rampah Sub-district, Serdang Bedagai Regency from March to May 2021. This location was chosen because it is a cassava-producing village. Determination of the sample using a random sample, ie all members of the population are assumed to have the same opportunity to be selected as the research sample. The data collection method used is observation, interviews and distributing questionnaires that have been tested for validity and reliability. To determine the level of adoption, a Likert scale model was used and to determine the factors that influence adoption, multiple linear regression analysis models were used. Based on the results of the study, it was found that the adoption rate of farmers in the use of superior varieties of Malaysian cassava in Sei Rampah Sub-district was very, simultaneously the variables of innovation characteristics (X1), communication media (X2), the role of extension workers (X3) and the role of farmer groups (X4) together -equally significant effect on farmer adoption in the use of Malaysia cassava varieties, while partially the factors that significantly influence are the characteristics of innovation (X1), communication media (X2) and the role of farmer groups (X4) while the non-significant influence is the role of extension worker (X3).